Cariprazine for the Adjunctive Treatment of Major Depressive Disorder: Results of a Randomized Phase 3 Placebo-Controlled Study (Study 301). (April 2023) - Sachs, Gary S.; Yeung, Paul P.; Rekeda, Ludmyla; Khan, Arifulla; Adams, Julie L.; Fava, Maurizio
Abstract: Background: Patients with major depressive disorder (MDD) often do not respond to antidepressant (ADT) monotherapy; adjunctive treatment is often used to address this unmet need. Cariprazine (CAR), a dopamine D3 -preferring D3 /D2 and serotonin 5-HT1A receptor partial agonist approved to treat adults with manic, mixed, or depressive episodes of bipolar I disorder, is under investigation as adjunctive therapy for patients with MDD. Methods: This randomized, double-blind, phase 3 placebo (PBO)-controlled study assessed the efficacy, safety, and tolerability of CAR 1.5 and 3 mg/d as an adjunct to ADT in adult patients with MDD (18–65 years) and inadequate response to ADT alone (NCT03738215). The primary endpoint was change from baseline to week 6 in Montgomery-Åsberg Depression Rating Scale (MADRS) total score. Hamilton Depression Rating Scale (HAMD-17), Hamilton Anxiety Rating Scale (HAM-A), and Clinical Global Impressions (CGI) were also assessed. Treatment response was defined as at least 50% decrease in MADRS total score at week 6. Results: Patients (n=751) in the modified intent-to-treat population were randomly assigned to CAR 1.5 mg/d+ADT (n=250), CAR 3 mg/d+ADT (n=252), or PBO+ADT (n=249). Mean age was 44.8 years and 73.4% were female; mean baseline total scores were: MADRS=32.5, HAMD-17=25.9, HAM-A= 21.4. Overall, 89.7% of patients completed the study; rates of discontinuation due to adverse events (AEs) and lack of efficacy were 3.6% and 0.5%, respectively. The difference in MADRS total score change from baseline to week 6 was statistically significant after multiplicity adjustment for CAR 1.5 mg/d vs PBO (-14.1 vs -11.5; adjusted P =.0050), but not for CAR 3 mg/d (-13.1; P =.0727). Differences for CAR 1.5 mg/d vs PBO were observed by week 2 (nominal P =.0453) and maintained at weeks 4 (nominal P <.0001) and 6 (nominal P =.0025). At week 6, more CAR 1.5 mg/d patients (44%) than PBO patients (34.9%) responded to treatment (nominal P =.0446). Greater improvement in the CGI-I scores was observed for CAR 1.5 (nominal P =.0026) and 3 mg/d (nominal P =.0076) vs PBO. At week 6, improvement in HAMD-17 total score reached nominal significance for CAR 1.5 mg/d vs PBO (-13.1 vs -11.1; nominal P =.0017), but not for CAR 3 mg/day (-12.2; P =.0783). HAM-A improvement was greater for CAR 1.5 mg/d vs PBO (nominal P =.0370). There were no deaths; 2 serious AEs occurred in each group (CAR: kidney infection, social stay hospitalization; PBO: depression, multiple sclerosis). The most common CAR AEs (≥5% and twice PBO) were akathisia and nausea. Conclusion: Cariprazine 1.5 mg/d was effective as adjunctive treatment in adults with MDD and inadequate response to ADT. Cariprazine was generally well tolerated, with a safety profile that was consistent with other indications. Together with results from a prior flex-dose study, these results suggest that adjunctive cariprazine may be an effective option for patients with inadequate response to ADT alone. Funding: AbbVie